Involvement of Pre-limbic Cortex-Nucleus accumbens projections in Context-Induced alcohol seeking - Bianchi, Paula Cristina; Palombo, Paola; Engi, Sheila Antonagi; Carneiro de Oliveira, Paulo Eduardo [UNESP]; Tavares, Gabrielle Emily Boaventura; Anjos-Santos, Alexia; Yokoyama, Thais Suemi; Planeta, Cleopatra da Silva [UNESP]; Cruz, Fábio Cardoso; Leão, Rodrigo Molini (Elsevier, 2024)
Alcohol use disorder (AUD) remains a critical public health issue worldwide, characterized by high relapse rates often triggered by contextual cues. This research investigates the neural mechanisms behind context-induced reinstatement of alcohol-seeking behavior, focusing on the nucleus accumbens and its interactions with the prelimbic cortex, employing Male Long-Evans rats in an ABA renewal model. In our experimental setup, rats were trained to self-administer 10 % ethanol in Context A, followed by extinction of lever pressing in the presence of discrete cues in Context B. The context-induced reinstatement of ethanol-seeking was then assessed by re-exposing rats to Context A or B under extinction conditions, aiming to simulate the environmental cues’ influence on relapse behaviors. Three experiments were conducted: Experiment 1 utilized Fos-immunohistochemistry to examine neuronal activation in the nucleus accumbens; Experiment 2 applied the baclofen + muscimol inactivation technique to probe the functional importance of the nucleus accumbens core; Experiment 3 used Fos-immunofluorescence along with Retrobeads injection to investigate activation of neurons projecting from the prelimbic cortex to the nucleus accumbens core. Our findings revealed significant increases in Fos-immunoreactive nuclei within the nucleus accumbens core and shell during the reinstatement phase in Context A, underscoring the environment's potent effect on ethanol-seeking behavior. Additionally, inactivation of the nucleus accumbens core markedly reduced reinstatement, and there was a notable activation of neurons from the prelimbic cortex to the nucleus accumbens core in the ethanol-associated context. These results highlight the critical role of the nucleus accumbens core and its corticostriatal projections in the neural circuitry underlying context-driven ethanol seeking.
Keywords: Alcohol; Pre-limbic Cortex-Nucleus Accumbens Projections; Rats; Reinstatement; Self-administration